2015
DOI: 10.1002/pits.21884
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Quality of Tier 1 Reading Instruction: Using Performance Feedback to Increase Opportunities to Respond During Implementation of a Core Reading Program

Abstract: Recent data on reading achievement indicates that a majority of young students are reading below proficiency. However, current research has shown that providing students with quality, research‐based reading instruction can help prevent many reading difficulties. Through the use of core reading programs, teachers have tools available to be able to provide students with evidence‐based instruction in the Tier 1 setting. However, classroom teachers need support in instructing core reading programs with the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Another potential challenge to the expression of differences in rate of OTR delivery is the difficulty associated with delivering OTRs at “recommended” rates. Although a standard recommendation for the ideal rate of OTR delivery is 4.00 to 6.00 prompts per minute for the presentation of new material and 8.00 to 12.00 prompts per minute for review (Council for Exceptional Children [CEC], 1987; Gunter et al,1998; Simonsen et al, 2008; Sutherland, Adler, & Gunter, 2003), the rate of OTR found in the empirical literature tends to fall below these recommended rates during intervention conditions (e.g., 3.35/minute [Haydon, Mancil, & Loan, 2009]; 1.71-2.59/minute [Cuticelli et al, 2015]; 3.52/minute [Sutherland et al, 2003]). That is, after specific training and support to increase the frequency of OTRs, participants in these studies fell below the recommended rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential challenge to the expression of differences in rate of OTR delivery is the difficulty associated with delivering OTRs at “recommended” rates. Although a standard recommendation for the ideal rate of OTR delivery is 4.00 to 6.00 prompts per minute for the presentation of new material and 8.00 to 12.00 prompts per minute for review (Council for Exceptional Children [CEC], 1987; Gunter et al,1998; Simonsen et al, 2008; Sutherland, Adler, & Gunter, 2003), the rate of OTR found in the empirical literature tends to fall below these recommended rates during intervention conditions (e.g., 3.35/minute [Haydon, Mancil, & Loan, 2009]; 1.71-2.59/minute [Cuticelli et al, 2015]; 3.52/minute [Sutherland et al, 2003]). That is, after specific training and support to increase the frequency of OTRs, participants in these studies fell below the recommended rates.…”
Section: Discussionmentioning
confidence: 99%
“…Increased OTRs can reduce problematic behavior and increase academic performance (Macsuga-Gage, & Simonsen, 2015; Sutherland & Wehby, 2001). Specific techniques for providing OTRs that have been identified in the literature include (a) individual responding to teacher prompt (Gardner, Heward, & Grossi, 1994; Haydon, Conroy, Scott, Sindelar, Barber, & Orlando, 2009), (b) verbal choral responding (Cuticelli, Collier-Meek, & Coyne, 2015; Haydon, Conroy, et al, 2009; Haydon, Mancil, & Loan, 2009; Macsuga-Gage & Simonsen, 2015), (c) response cards or white boards (Cuticelli et al, 2015), and (d) electronic response systems (Macsuga-Gage & Simonsen, 2015). In their review of the literature, MacSuga-Gage and Simonsen (2015) found positive student outcomes across all grade levels associated with the delivery of frequent OTRs.…”
Section: Otrsmentioning
confidence: 99%
“…The Council for Exceptional Children (CEC) has suggested an approximate frequency for OTR in the classroom. An opportunity to respond (OTR) is a situation where a teacher is interacting with the students by providing them the chance to give a response-for example, posing questions for students to answer by a nod, raising of hand, quick writing, or command (Cuticelli, Collier-Meek, & Coyne, 2016). These opportunities could be presented to individual students or provided in a group setting.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities to respond enhance interactivity between students and teachers, alertness, engagement, and understanding. Thus, OTR has been shown to improve students' outcomes (Cuticelli, Collier-Meek, & Coyne, 2016). For instance, the CEC has recommended four to six OTR per minute for students who have a high incidence of disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Performance feedback is generally defined as the provision of information about teacher's quality and/or quantity of practices based on observation of their implementation (Fallon et al, 2015; Snyder et al, 2012). Within educational settings, performance feedback generally consists of meetings with teachers to discuss their fidelity of curriculum implementation and/or use of practices (Cuticelli et al, 2016; Snyder et al, 2012). Based on a teacher's performance, coaches support them through strategies such as praise, reflection, modeling, and role‐play to help improve and/or sustain their practices (Albritton et al, 2018; Barton & Worley, 2007; Conroy et al, 2014; Fox et al, 2011; Snyder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%